The importance of data issues when comparing cystic fibrosis registry outcomes between countries: Are annual review FEV(1) in the UK only collected when subjects are well? - Hoo, Zhe Hui (J Eval Clin Pract, 2018)
RATIONALE, AIMS AND OBJECTIVE: Cross‐country comparisons of cystic fibrosis (CF) outcomes can potentially identify variation in care but are dependent on data quality. An important assumption is that the UK annual review FEV(1) is only collected during periods of clinical stability. If this assumption does not hold, results of FEV(1) comparisons may be biased in favour of registries with encounter‐based FEV(1). We aimed to test the assumption that CF annual reviews in the UK are only performed during periods of clinical stability. METHOD: Prospective encounter‐based data collected in Sheffield (n = 174) was used to establish whether annual review FEV(1) were always collected during periods of clinical stability and to determine the group‐level discrepancy between annual review vs best FEV(1). We then went on to quantify the group‐level discrepancy between annual review and best annual FEV(1) readings within the UK registry (n = 2995) to determine if the differences observed in Sheffield also apply to the wider UK data. RESULTS: Sheffield results showed a group‐level discrepancy between best and annual review FEV(1) of −2.5% (95% CI −3.95% to −1.2%) for annual reviews performed during periods of clinical stability (n = 50). The group‐level discrepancy is larger at −8.0% (95% CI −11.2% to −4.9%) among annual reviews performed during periods of clinical instability (n = 13). Therefore, the magnitude of this group‐level discrepancy is a surrogate for the proportion of clinically stable annual reviews—smaller discrepancy indicates a higher proportion of clinically stable annual reviews and vice versa. The overall group‐level discrepancy in the UK registry (−5.6%, 95% CI −5.9 to −5.4%) was similar to Sheffield (−6.1%, 95% CI −7.1 to −5.1%). Around 20% of the clinician reviewed, annual reviews in Sheffield were performed during periods of clinically instability. CONCLUSIONS: Annual review FEV(1) underestimates lung health of adults with CF in the UK and may bias cross‐country comparisons.